Coercivity mechanism of melt-spun Sm(Fe11Ti) - COEY, JOHN MICHAEL DAVID (IEEE, 1990)
Hysteresis loops of randomly oriented grains with uniaxial anisotropy were computed on the basis of an array of 27 Wigner-Seitz cells representing crystallites which interact by exchange coupling at the grain boundaries. The computed coercivity increases linearly with increasing interatomic exchange. Using the experimental anisotropy and exchange parameters for Sm(Fe11Ti), the authors found ? 0Hc=1.2 T, which agrees well with results on melt-spun ribbon. The main insight is that strong intergrain coupling is beneficial for developing coercivity in nanocrystalline alloys with uniaxial anisotropy
PUBLISHED
Keywords: Physics